2004
DOI: 10.1016/j.rmed.2004.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of inflammatory mechanisms on the redox balance in interstitial lung diseases

Abstract: This study investigated the hypothesis that inflammatory, regulatory and antioxidant systems control the redox balance in interstitial lung diseases. Spontaneous mRNA expression of inflammatory cytokines and redox-active enzymes was examined in bronchoalveolar lavage (BAL) cells from patients with idiopathic pulmonary fibrosis (IPF) and sarcoidosis (SARC) using RT-PCR analysis. Pulmonary oxidative stress was characterized by carbonyl-levels in the soluble BAL-fluid protein. Protein carbonyls were normal in SAR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
10
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
4
10
0
1
Order By: Relevance
“…Using freshly isolated BAL cells, this study found no significant differences in TGF-b1 mRNA levels between patients and normal samples. However, increased transcripts levels of the anti-inflammatory cytokine IL-10 were noted, which is in line with other studies [4,6]. The data on TNF-a and IL-12p40 indicate that pulmonary cells other than BAL cells can produce and secrete these cytokines, as they differed significantly in patient and control BALF but not BAL cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Using freshly isolated BAL cells, this study found no significant differences in TGF-b1 mRNA levels between patients and normal samples. However, increased transcripts levels of the anti-inflammatory cytokine IL-10 were noted, which is in line with other studies [4,6]. The data on TNF-a and IL-12p40 indicate that pulmonary cells other than BAL cells can produce and secrete these cytokines, as they differed significantly in patient and control BALF but not BAL cells.…”
Section: Discussionsupporting
confidence: 90%
“…As with previous studies on pulmonary sarcoidosis that demonstrated elevated expression of Th1 cytokines IL-2 and IFN-c, and showed little or no detectable expression of Th2 cytokines in BAL cells [3,24], these results are in line with a preferential Th1 cytokine expression at sites of disease in sarcoidosis. No significant changes in the transcript levels for TNF-a or IL-12p40 were found in BAL cells from sarcoidosis patients, which contrasted with some previous studies [24,25] but was in line with others [4,7,26,27]. Such discrepancies can depend on the choice of patient group, including smoking habits or previous/ongoing treatment, and the sensitivity of the methods.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…23,24 Our observations that neutrophils may play a leading role in pulmonary protein damage are in line with data showing that a low IL-10/IL-8 mRNA ratio is paralleled with significant oxidative stress in ILD. 25 Neutrophils play a central role in local pulmonary host defenses, and their persistence in the alveolar compartment may lead to excessive inflammation and oxidative damage. Eosinophils may play a similar role, but were unlikely to have contributed to protein oxidation in the children studied because eosinophils were rarely present in the BAL fluid.…”
Section: Oxidation Pattern Of Bal Proteinsmentioning
confidence: 99%
“…An example is idiopathic pulmonary fibrosis (IPF), a disease characterized by fatal prognosis due to massive lung fibrosis and unresponsiveness to treatment [1]. Increased ex-vivo production of superoxide anion or hydrogen peroxide by cells from bronchoalveolar lavage (BAL) have also been reported in sarcoidosis [2, 3], but secondary markers of oxidative stress, such as oxidized proteins, or oxidized methionine residues in BAL fluid (BALF) are not increased in sarcoidosis, contrary to IPF [46]. …”
Section: Introductionmentioning
confidence: 99%